The contribution of the immigrant population to the U.S. long-term care workforce. (October 2020) - Rapp, Thomas; Sicsic, Jonathan
Abstract: The long-term care (LTC) sector will soon face a shortage of care workers. The consequences are potentially dramatic, urging the need to design policies aiming at reducing the turnover rate of LTC workers. Immigrant workers are an important part of the LTC workforce. Pooling data from the Annual Social and Economic (ASEC) supplement to the Current Population Survey (CPS) for years 2003–2019, we compare US-born and immigrant LTC workers' propensity to stay in the LTC workforce over one year. We distinguish two categories of LTC workers: personal care workers and nurses. We show that for both categories, naturalized citizens, legal noncitizen immigrants, and unauthorized immigrants have a higher probability of staying in the LTC workforce compared to US-born citizens. We provide two potential explanations: we show that immigrant personal care workers are more likely to report a better health, and that immigrant nurses have a lower wage variation sensitivity. Our results also suggest that wage increases are likely to be associated with higher retention rates in the profession. Highlights: In the United-States, the LTC sector faces a shortage of care suppliers. Immigrants are more likely to stay into the LTC workforce than US-born workers. Priority should be given to policies increasing hourly wages in the LTC sector.